Gastric Diagnosis Expert System using the Fuzzy Mamdani Method - Rozizah Dwi Gusni; Eva Rianti; Firna Yenila (Universitas Putra Indonesia YPTK Padang, 2023)
The stomach is one of the important digestive organs in humans. Gastric disease is inflammation of the stomach lining caused by microorganisms, this disease is caused more by Helycobacterpylori bacteria, apart from being caused by bacteria, stomach disease can also be caused by irregular lifestyle and eating patterns. Diseases that attack the stomach are still considered trivial by the general public, so not many people know about stomach diseases and the symptoms that exist. This is what causes people to be reluctant to see a doctor when they suffer from pain that attacks the stomach. When a disease attacks the stomach, people only use experience or intuition to cure it, so it is not treated properly. By using an expert system, patients can save time going to the hospital and can improve service to patients. The results of the Mamdani fuzzy logic calculations require a report on the possibility of stomach disease suffered by the user/patient, examples of possibilities are small, somewhat large and large based on the highest value results. It is hoped that with this system, it will be easier for patients to diagnose gastric diseases to carry out prevention and early diagnosis and treatment.